HUBUNGAN ANCAMAN YANG DIRASAKAN DENGAN UPAYA MENCEGAH BAHAYA ROKOK BAGI KESEHATAN REMAJA DI DESA HUTARAJA KECAMATAN SIABU KABUPATEN MANDAILING NATAL TAHUN 2015 - Lusiani, Yetti; Hasny, Hasny; Sondang, Sondang; Salwah, Salwah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2015)
Smoking tends to be favored by men, including women. “89% of smokers are adolescences who are influenced by advertisement,” said the Secretary General of Child Protection, Arist Merdeka Sirait. The National Socio-Economic Survey in 2009 states that the highest adolescence group between 15 to 19 years old that smoke reaches to 63.7%.The research used analytic method with cross sectional  design.  The samples were 30 adolescences, taken by using simple random sampling technique. The data consisted of  primary and secondary data. Primary data were gathered by using questionnaires about the threat and effort to forestall the danger of smoking. The gathered data were analyzed by using univatriate analysis and bivatriate analysis with chi square statistic test. The result of the research showed that 22 respondents (73.3%) were threatened by the danger of smoking, and 8 respondents (26.7%) were not, while 8 respondents (26.7%) attempted to forestall the danger of smoking for dental health and 22 respondents (73.3%) did not.The result of chi square test showed that there was no significant correlation between the variable of threat and the variable of effort to forestall the danger of smoking for adolescences’ dental health (p = 3.55). The threat felt by adolescences did not influence their effort to forestall the danger of smoking for their dental health.